Effectiveness of lemongrass leaf extract (Cymbopogon citratus) as a root canal irrigation agent in removing smear layer: Effectiveness of lemongrass leaf extract (Cymbopogon citratus) as a root canal irrigation agent in removing smear layer - Mattulada, Indrya Kirana; Aldilawati, Sari; Syam, Syamsiah; Bima, Lukman; Hamka, Amira Luthfiyah (Makassar Dental Journal, 2025)
Smear layer (SL) cleaning is considered a very important aspect of root canal treatment (RCT) as the SL can act as a substrate for microbial proliferation. In addition, SL has the potential to affect the adaptation of the sealer to the root canal walls and its pene-tration of the dentinal tubules. Lemongrass (Cymbopogon citratus) contains flavonoids, tripenoids/steroids, saponins, alkaloids, tannins, phenolics and essential oils. This article presents research on the ability of lemongrass leaf extract (LLE) as a root ca-nal irrigation material in removing SL. This study used an experimental post-test only control design. Samples were taken by purpo-sive sampling technique with 4 treatment groups of 6 repetitions. Based on the Mann-Whitney test, the p-value was 0.495 at ⅓ apical, 0.269 at ⅓ middle and 0.575 at ⅓ coronal (p-value>0.05). The results showed that there was no significant difference between the 17% EDTA treatment group and 20% LLE on the level of SL cleanliness. It was concluded that 20% LLE was ef-fective in removing smear layer.